ARL6IP1 mutation causes congenital insensitivity to pain, acromutilation and spastic paraplegia. Issue 1 (31st August 2017) - Nizon, M.; Küry, S.; Péréon, Y.; Besnard, T.; Quinquis, D.; Boisseau, P.; Marsaud, T.; Magot, A.; Mussini, J.‐M.; Mayrargue, E.; Barbarot, S.; Bézieau, S.; et al.
Abstract : Hereditary sensory and autonomic neuropathies (HSAN) type II are characterized by autosomal recessive inheritance, onset at birth and self‐mutilating behavior. Here, we described a new patient with congenital insensitivity to pain, sensory neuropathy, acromutilation, and spastic paraplegia. Whole‐exome sequencing showed a homozygous frameshift variant c.[577_580del], p.(Lys193Phefs*37) in ARL6IP1 . The protein harbors reticulon‐like short hairpin transmembrane domains and has a role in endoplasmic reticulum shaping. The variant causes an additional C‐terminus hydrophobic domain which could disrupt its function. ARL6IP1 interacts with atlastin‐1 responsible for SPG3A and HSAN type ID. This report highlights the role of ARL6IP1 in the pathophysiology of insensitivity to pain and spastic paraplegia. Abstract :